(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the role of the government in empowering brick entrepreneurs in Gentungang Village, Bajeng Barat District, Gowa Regency. The type of research used in this study was descriptive qualitative using primary data and secondary data. selected based on the view that the informant has knowledge and information about the problem under study.The results of this study indicate that the empowerment of the brick-making community in the village of Gentungang. In terms of: (a) the role of the government in regulations that have been pursued by the government, namely freeing the community from all factors that can hinder the brick-making business (b) the role of the government in dynamism namely providing guidance and training so that the business they run does not fall into a weakening condition. (c) The role of the Government as a facilitator is to provide solutions in providing counseling and training as well as assisting in marketing the bricks they have managed so far.